(untitled) (Architecture Image Studies, 2025)
Rice production is increasingly under threat by a serious fungal disease in the Chidambaram region of Cuddalore district, especially false smut, sheath blight, and brown spot, which are becoming more severe under global climate change. Usually, farmer do their inspections at a later stage, which causes critical damage to the rice crops. This manual inspection is error-prone, time-consuming, and subjective. In these situations, AI-enabled tools and methods are essential for accurate and timely rice disease prediction. This research introduces a novel approach using deep learning–driven image classification framework for accurate detection of rice plant diseases (DLDICF-ADRPD). The DLDICF-ADRPD undergoes three different stages, namely data collection, data preprocessing, feature extraction, detection and classification of diseases. This combination leads to an efficient and robust disease classification system. The series of experiments was conducted to assess the proposed DLDICF-ADRPD performance using large dataset of rice leaf images from different disease types and growth phases, obtained from the publicly accessible Kaggle datasets. When compared to other existing disease prediction models, our DLDICF-ADRPD model performs better. Overall, the suggested DLDICF-ADRPD design greatly increases the reliability and accuracy of disease recognition, supporting global food security and sustainable agriculture.